Application of the Customers Satisfaction Index (CSI) and Importance Performance Analysis (IPA) Methods to Measure Reader Satisfaction with the Quality of Website Services Indodaily.co - Chindi Seftylia; Widya Cholil (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
satisfaction and trust are indeed the most dominant problems in online news media, but the process to meet the reader's satisfaction is not easy. Because, there are many factors that can influence the achievement of the level of reader satisfaction. The quality of service provided will be one of the dominant factors that are considered by the reader on the level of perceived satisfaction. Through this study, the author aims to determine the level of reader satisfaction with the service quality of the Indodaily.co website by using the Customer Satisfaction Index (CSI) method to determine the level of reader satisfaction and the Importance Performance Analysis (IPA) method is used to determine the level of importance of each service attribute and priority. improvements that must be made by the Indodaily.co website. The results obtained from the Customer Satisfaction Index (CSI) method show that the overall level of satisfaction of Indodaily.co website visitors is included in the "Very Satisfied" category. While the calculation results are based on the Importance Performance Analysis (IPA) method, there are two attributes that need to be improved, seven attributes that must be maintained and ten attributes that need to be reduced in intensity by the Indodaily.co website.